PENGEMBANGAN POTENSI SAGU SEBAGAI PANGAN LOKAL DALAM UPAYA MEWUJUDKAN DESA MANDIRI PANGAN DI DESA TUADA, KABUPATEN HALMAHERA BARAT - Hamidin Rasulu; Nurjanna Albaar; Hasbullah; Mila Fatmawati; Gunawan; Abdul Kadir Kamaluddin; Johan Fahri (Jurnal Abdi Insani, 2026)
The development of sago as a local food source in Tuada Village, West Halmahera Regency, aims to realize an independent food village based on local potential. The purpose of this activity is to increase the use of sago as a local food through socialization activities, training in processing sago-based products, and strengthening community capacity in the development of local food businesses in Tuada Village, West Halmahera Regency. The main activities include strengthening the capacity of Marimoi MSMEs in managing sago processing businesses, which enable the community to improve entrepreneurial skills. This activity also includes counseling, training on the practice of processing sago into various food products, as well as assistance in economic, financial and marketing analysis to community groups. Education on the application of sago manufacturing methods to ensure food quality and safety, so that sago-based products can meet higher market standards. In addition, knowledge transfer on innovative processing techniques for sago products, macaroni products and sago egg snacks. This program also emphasizes strengthening the community's economic institutions through collaborative product marketing strategies, thereby expanding market reach and strengthening the position of local products. Applied technologies such as processing equipment and business management, packaging, and promotional strategies. Household-scale sago flour production and product diversification showed positive results from technical, financial, and economic perspectives. The development of sago not only contributes to local food security but also plays an important role in improving community welfare and strengthening the economy of Tuada Village.